Ag-Incentives: A global database monitoring agricultural incentives and distortions to inform better policies - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2021)
In both developed and developing countries, governments often intervene in the agriculture sector to support development and to respond to political-economy pressures, using trade policies or price support for particular agricultural commodities. To understand the full implications of agricultural policies, it is necessary to correctly measure the extent to which policies and their derivatives distort market prices of commodities, and to understand the implications of protection provided to other sectors that affects agricultural incentives through real exchange rate impacts. Multiple international organizations (IOs) provide assessment and measurement of agricultural incentives. However, a comprehensive and long-term global database would enable analysts and policymakers to compare and interpret the impact of across commodities, countries, and time. To facilitate construction and dissemination of such a database, the Ag-Incentives Consortium was formed in 2013 to bring together institutional efforts, including those of the Inter-American Development Bank, International Food Research Institute (IFPRI), Monitoring and Analysing Food and Agricultural Policies program of the Food and Agriculture Organization of the United Nations (FAO-MAFAP), Organisation for Economic Co-operation and Development (OECD), and World Bank, as well as the CGIAR Research Program on Policies, Institutions, and Markets (PIM). The Ag-Incentives Consortium is the “International Organizations Consortium for Measuring the Environment for Agriculture” and is based on the Memorandum of Understanding for Co-operative Activities on Agricultural Incentives Measurement signed by OECD, FAO-MAFAP, IDB, World Bank, and IFPRI. The Consortium has been supported by funding from PIM.